IL‐4/IL‐13‐producing ILC2s are required for timely control of intestinal helminth infection in mice. Issue 12 (28th September 2022) - Varela, Filipa; Symowski, Cornelia; Pollock, Jonathan; Wirtz, Stefan; Voehringer, David
Abstract: Infection of mice with Nippostrongylus brasiliensis ( Nb ) serves as a model for human hookworm infection affecting about 600 million people world‐wide. Expulsion of Nb from the intestine requires IL‐13‐mediated mucus secretion from goblet cells and activation of smooth muscles cells. Type 2 innate lymphoid cells (ILC2s) are a major cellular source of IL‐13 but it remains unclear whether IL‐13 secretion from ILC2s is required for Nb expulsion. Here, we compared the immune response to Nb infection in mixed bone marrow chimeras with wild‐type or IL‐4/IL‐13‐deficient ILC2s. ILC2‐derived IL‐4/IL‐13 was required for recruitment of eosinophils to the lung but had no influence of systemic eosinophil levels. In the small intestine, goblet cell hyperplasia and tuft cell accumulation was largely dependent on IL‐4/IL‐13 secretion from ILC2s. This further translated to higher eggs counts and impaired worm expulsion in mice with IL‐4/IL‐13‐deficient ILC2s. Overall, we demonstrate that ILC2s constitute a non‐redundant source of IL‐4/IL‐13 required for protective immunity against primary Nb infection. Abstract : ILC2‐derived IL‐4/IL‐13 plays a non‐redundant role for eosinophil recruitment to the lung and expulsion of N. brasiliensis worm parasites from the intestine.